PERANCANGAN APLIKASI ANDROID E-COMMERCE KPRI UNP MART - Jeffri Agustiar; Efrizon Efrizon; Denny Kurniadi (Universitas Negeri Padang, 2019)
This paper aims to resolve the transaction problems at the KPRI UNP mart which are still going on manually and require the buyer to come to the mart to buy the items to be purchased. Bookings should be able to use smartphones through the use of applications so that customers can make transactions immediately. The waterfall method is used for designing client-based applications and the Object Orientit Programing (OOP) method, besides the application applies the OOP-based Model View Controller (MVC) technique. Server-side applications use the Framework Code Igniter (Framework CI) with the main language PHP equipped with the use of the json web and MySQL DBMS. Application on the client side uses the Java Java Development Kit (JDK). Designing an e-commerce android application KPRI UNP mart has 3 application results, the first application 1 application on the server that manages management for the client, the second 1 client buyer application that is used to view goods information and ordering, third 1 sending client application used to retrieve order the buyer and deliver it.Keywords: Android, e-commerce, KPRI, client-server, framework CI